Pursuing Happiness in Eat Pray Love Movie (2010) Directed by Ryan Murphy: a Psychoanalytic Approach - Aulia Novika, Rutama; Candraningrum, Dewi; Setyabudi, Titis (JoLLIET, 2014)
This movie is true story of Elizabeth Gilbertâs life that adapted from her novel. This movie tells about Lizâs journey for a year that visit three counties to pursue her happiness. The research is proposed to analyze pursuing happiness of Liz Gilbertâs personalities in facing her depression with Psychoanalytic Approach.Â The objective of the study isÂ to analyze the film based on the psychoanalytic approach.Â This study is a descriptive qualitative study, using the movie of Ryan MurphyâsÂ Eat Pray Love. AndÂ Eat Pray Loveâs major character as the object of analysisÂ of the study. The researcher makes an analysis of Liz Gilbertâs id, ego, and superego. The researcherÂ uses the theory of Psychoanalytic by Sigmund FreudÂ because it is relevant to the problem. Based on the analysis, the outcome of this study shows the following conclusion. Firstly, there is a close relationship between a work of literature and Psychoanalysis Phenomena. Secondly, the general conclusion of psychoanalysis of humans is when people get desperate then they pursue the happiness.